The general as statesman : exploring the professional need for commanders to support viable political outcomes in peace and stability operations as typified by the UK military approach - Lovelock, R. (Cranfield University, 2011)
The problem of theatre level politico-military arrangements during peace and stability operations is important because the intervening actors, working in complex and often ambiguous circumstances, need to calibrate the application of military and political means as a coherent interdependent whole. This is necessary in order to build peace, secure viable political outcomes and hence strategic successes; however it is not easy in practice. This thesis examines the hypothesis that, beyond their security-related tasks, military commanders should provide direct support to civilian interlocutors in order to facilitate and sustain the local political process. This requires military co-operation with other relevant actors, responsiveness to political direction and the specific shaping of military operations to impact decisively on political outcomes. This work establishes that Western and United Nations doctrinal guidance extols political primacy and civil-military cooperation but does not fully explain the central importance of the political process, nor does it capture the potential peace building role of the military component. Analysis of practice in Kosovo, Iraq and Afghanistan, suggests that military commanders retain a uniquely influential position and have generally used their military means to positively influence political progress and help coordinate multi-dimensional plans. On occasion, to secure momentum and fill a void, commanders have quietly assumed a political function. Doctrine now needs to be refreshed to reflect practice. It should explain the military role in supporting the political process, elaborate the politico-military relationship as the inner core of a comprehensive approach to peace building and provide candid guidance on the difficulties to be expected where politico-military and coordination arrangements are incoherent. Moreover further work is needed on the wider application of this doctrine by the United Nations and the preparation of civilian leaders for politico-military relationships.